The Effect of Social Support on Glycemic Control in Patients with Type 2 Diabetes Mellitus: The Mediating Roles of Self-Efficacy and Adherence - Yechang Shao; Lu Liang; Linjing Shi; Chengsong Wan; Shouyi Yu (Journal of Diabetes Research)
Ample evidence suggests that social support, self-efficacy, and adherence significantly, independently, and together affect glycemic control in patients with type 2 diabetes mellitus (T2DM), but the pathway from social support to glycemic control remains unclear. This study hypothesized that the effect of social support on glycemic control was mediated sequentially by self-efficacy and adherence. Patients with T2DM were recruited from two hospitals in Guangzhou, China, from January 1 to July 31, 2014, and their sociodemographic clinical data and their assessments on social support, self-efficacy, and adherence were obtained from medical records and self-completed questionnaires. Of the 532 patients who participated, 35% achieved glycemic control (i.e., HbA1c < 7%). Social support, self-efficacy, and adherence had significant correlations with each other and with glycemic control (P<0.05). Regression analyses and structural equation modeling showed that better social support was associated to better patient self-efficacy, which, in turn, was associated with better medical adherence, which was associated with improved glycemic control, and the relationship between social support and glycemic control was sequentially and completely mediated by self-efficacy and adherence. The five goodness-of-fit indices confirmed that our data fitted the hypothesized pathway model strongly.